Masyarakat petani kelapa dan ibu PKK Kelurahan Tonyamang Kecamatan Patampanua Kabupaten Pinrang - Muhammad Syahrir; Netti Herawati; Muhammad Yunus; Nita Maghfirah Ilyas (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Community Coconut farmers and mother of PKK Kel. Tonyamang Kec. Patampanua Pinrang Regency is generally do not have the knowledge and skills to process a considerable amount of coconut water waste in the area into useful materials such as food vinegar and ethanol, which can increase economic value, especially in the farming community in the area. The approach taken is to provide training and empowerment to mother of PKK and coconut farmers in the form of lectures and live demonstrations and practices at partner locations, on thecniq for processing coconut water waste into chemicals in the form of ethanol and food vinegar, so that they are skilled in conducting training and can develop further. The output of PKM is food vinegar and ethanol from high quality coconut water waste for the needs of the community in partner areas and can even be marketed to other regions.